Advocating for Mediation as a means of addressing underlying issues with Discipline at Public High Schools in South Africa - Tshifularo, Muofhe (Department of Commercial Law, 2023)
This paper discusses whether the disciplinary process in public high schools in South Africa achieves the purpose envisioned in the Schools Act. The purpose is to establish a disciplined schooling environment in which learners take responsibility for their behaviour and promote self-discipline. To establish positive discipline. However, according to research, the current disciplinary process has failed to teach learners about responsibility and self-discipline. This paper. through literature review, analyses the challenges in the current laws relating to school discipline. The first challenge is that the current disciplinary proceeding is retributive and adversarial. This is not in line with positive discipline. The second challenge is that suspensions are not in the best interest of the child. Thus, to address these challenges, consideration is given to the inclusion of peer mediation into the high school disciplinary process. Peer mediation has been successfully integrated in New Zealand and the United States and has resulted in an improved sense of responsibility and a positive school environment. Thus, it is argued that integrating peer mediation as a preliminary step in the high school disciplinary process would help teach learners responsibility and self-discipline.